ARTIKEL REVIEW: PERAN GURU DALAM PERKEMBAANGAN TEKNOLOGI PENDIDIKAN DI ERA DIGITAL - Ardiansyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to examine the role of teachers in the development of educational technology in the digital era. Through a literature review, this study analyzes various literatures related to the integration of technology in education, innovative learning models, and teacher competency development. The results of the study show that teachers have a central role in the success of technology implementation in education. Teachers need to be actively involved in developing technology-based curricula, adopting hybrid learning models, developing students' soft skills, and utilizing technology-based assessment tools. In addition, collaboration with parents and the community is also important to support digital learning. This study concludes that with continuous training and adequate support, teachers can be effective facilitators in creating innovative and relevant learning environments for the 21st century.